Llaqtaqasa: aproximación al consumo de un poblado del Intermedio Tardío (1100-1400 D.C) en el distrito de Concepción, provincia Vilcas Huamán (Ayacucho) - Martínez Sulca, Winnie Celeste (2021)
Based on the state of knowledge of the sites of the Late Intermediate Period (1100-1400 A. P.) in the province of Vilcas Huamán, it was proposed to address the problem of domestic areas and their spatial organization through the study of the archaeological site Llaqtaqasa located in the Concepción district, Vilcas Huamán province (Ayacucho). To obtain data, prospecting works were carried out without collecting material in sector B, which included the topographic and planimetric survey of the entire area. During the execution of the same, the presence of a burrow at the foot of an enclosure could be registered, which was used to extract samples of land in order to obtain some data on the consumption of the inhabitants and see the relationship with the Andenería system and pens present in the settlement. All the data obtained shows that the residents of Llaqtaqasa had a complementary economy based on high-altitude agriculture and camelid farming, future research will corroborate what has been stated.